Factores determinantes de la expansión de la industria del calzado y su impacto en la gestión empresarial y productiva en el distrito de el porvenir : 2002-2008 - Cruz Mendoza, Luis Alberto (2011)
This research aims to analyze the expansion of the footwear industry and its impact on business management and production in the district of El Porvenir: 2002 - 2008, under the conditions of MSEs in the industry, have been business development. For this purpose, a sample was not random, considering Mypes that develop within the business formality. The sample consisted of one hundred seventy-seven companies in the footwear industry, of which one hundred twenty-four are linked to micro-and fifty-three small businesses. We developed a field study of non-experimental, considering methods: descriptive-longitudinal-inductive-deductive. Also, a questionnaire was self-standard characteristics of business and labor, according to managers Mypes. For the analysis of the results took into account historical data for the period 2002 - 2008, and surveys, which placed greater emphasis on the factors: organization, technology and production level. The results are very informative and solid, the same that tells us that the vast majority of employers surveyed are aware that training, the assimilation of new technologies, business management, and improve their attitude to competition, have been instrumental the get the relative expansion of micro and small enterprises in the footwear in the District El Porvenir Trujillo 2002-2008.